Decolorization of Metanil Yellow G by a halophilic alkalithermophilic bacterial consortium. (November 2020) - Guo, Guang; Hao, Jiuxiao; Tian, Fang; Liu, Chong; Ding, Keqiang; Zhang, Can; Yang, Feng; Xu, Jin
Highlights: A halophilic alkalithermophilic bacterial consortium was enriched. ZSY can decolorize azo dye at 10% salinity, pH10 and 50 °C. FTIR, GC–MS and enzyme analysis are used to study decolorization mechanism. Functional genes involved in degradation were identified by omics. Abstract: Increased temperature, salinity and alkalinity restrict the biodecolorization rate of textile wastewater. In the present study, the halophilic alkalithermophilic bacterial consortium ZSY, which can decolorize azo dyes under 10% salinity, pH 10 and 50 °C, was enriched. It can decolorize Metanil Yellow G (MYG) under a wide range of pH values (8–10), temperatures (40–50 °C), dye concentrations (100–400 mg/L) and salinity levels (1%–10%). Laccase (Lac), lignin peroxidase (Lip), nicotinamide adenine dinucleotide-dichlorophenol indophenol reductase (NADH-DCIP) and azoreductase are involved in the decolorization process. A decolorization pathway of MYG was proposed via gas chromatography–mass spectrometry (GC–MS) and Fourier transform infrared spectroscopy (FTIR). The toxicity of MYG decreased after decolorization by ZSY consortium. A metagenomic sequencing approach was subsequently applied to identify the functional genes involved in decolorization. Overall, this halophilic alkalithermophilic bacterial consortium could be a promising candidate for the treatment of textile wastewater in environments with increased temperature, salinity and alkalinity.